The New Kingdom of Egypt and the Early State Organizations of the Armenian Highland in the Second Half of the II Millennium Bc (Based on Historical Sources and Archaeological Evidence) - Ashot Piliposyan; Armine Hayrapetyan (Banber Arevelagitut'yan Instituti, 2025)
The Ancient Near Eastern powerful states in the mid II millennium BC were not only directing and supervising the military-political, trading-economic, and sociocultural processes, but were also trying to obtain their dominance and control in the region. This was the reason that two conflicting groups gradually polarized in the region, where each state, despite its interests concerning the redistribution of spheres of influence in the ancient Near East, had to ally a more convenient political formation, given the current political situation and its capacities. As a result, the Hittite New Kingdom, Arzawa and Wilusa appeared to be in one of the groups, and the New Kingdom of Egypt, Kassite Babylonia and Mitanni were in the other one. The interstate relations of these powers included both military-political and diplomatic rivalry, and a controlled system of well-organized transit trading and cultural relations. At the same time, each of the groups sought to urge other small early state organizations and tribal unions of the region to get involved in the alliance, contributing to the realization of prospective political plans with their capacities of raw materials, production of specific items and human resources. This was the situation also with the part of the early state organization of the Armenian Highland. Meanwhile, both the written sources and the archaeological excavations in general, testify the anti-Hittite orientation of the early state organizations of the Armenian Highland and their tending towards Egypt-Mitanni-Kassite Babylonia alliance.